Anthropometric characteristics, physical fitness, and throwing velocity in elite women's handball teams - Saavedra, J. M.; Kristjansdottir, H.; Einarsson, I. P.; Gudmundsdottir, M. L.; Porgeirsson, S.; Stefansson, A. (The Journal of Strength and Conditioning Research, 2018)
The aims of this study were (a) to analyze anthropometric, physical fitness, and throwing speed in women elite handball players of different ages and (b) to develop a multivariate model explaining handball performance from a multidimensional perspective. Eighty women handball players (18.2 ± 4.0 years in age) from national team selections participated in the study. The players belonged to A Team, under-19, under-17, and under-15 national teams. All were evaluated by basic anthropometry, physical fitness tests, and handball throwing speed. A 1-way analysis of variance was used to establish the differences between teams with a Bonferroni post hoc test. For each team, a discriminant analysis was performed to determine the predictor variables of performance. Pearson's simple correlation coefficients were calculated between each of the variables. The results of this particular study showed that (a) between the A Team and the U19 team, there were only differences in mass, countermovement jump (CMJ), medicine ball throw, and yo-yo test, (b) the A Team and U19 predictive models correctly classified 76 and 90% of the samples, respectively, with the variables involved being mass and body mass index (A Team) and 30-m sprint and 7-m throwing speed (U19 team), and (c) the 7- and 9-m throwing speeds were correlated with each other and with stature, mass, CMJ, and medicine ball throw (0.367 = r = 0.533; 0.001 = p = 0.05). These results could help improve coaches' knowledge of elite female teams, in particular, in the country where the study was conducted and in others of similar characteristics.